Tejuatsin tiueli okse taitol (and do you speak another language?) - Bianchini, Natalia (2023)
The objective of this work is to reflect on the convergence between the moderncolonial and the ancestral-indigenist within medicine, the social division of labor and gender violence in Cuetzalan del Progreso (Puebla, Mexico) and its communities from the perspective Latin American Marxism and community and rural feminisms. Methodologically, it is qualitative research that uses the Grounded Theory approach to analyze the case study, through participant observation, documentary review and in-depth semi-structured interviews with members of the Tosepan Pajti Health Cooperative. The results of the study contribute to understanding some aspects of the variegated social formation (heterogeneous, dynamic and contradictory) of that territory.